The legal basis of cryptocurrency regulation in Hong Kong: an analytical review and specific features ("Journal "U". Economy. Management. Finance.", 2025)
The article describes the main approaches to classifying virtual assets in Hong Kong, highlights the distinctive features of the regulatory framework for regulating cryptocurrencies in this country. The positive and negative aspects of cryptocurrency regulation in Hong Kong were noted.
Keywords: Hong Kong; crypto assets; utility tokens; security tokens; cryptocurrency